CRM success factors in Women Apparel Retail Outlets - THABASSUM, N. FATHIMA; D. RAJALAKSHMI (International Journal of Psychosocial Rehabilitation, 2020)
Customer relationship management (CRM) is a vital business strategy for all the businesses to survive and sustain. A successful customer relationship management leads to customer acquisition, customer retention, and increased customer loyalty which in turn increases the profit and enhances the sales of the organisation in which CRM is implemented. The study is conducted among 100 female customers of women apparel retail outlets in Thirupattur district of Tamil Nadu, India. Exploratory factor analysis is performed to find out the CRM success factors. Confirmatory factor analysis is done to know the consistency of the underlying constructs and two step cluster analysis is employed to segment the customers on the basis of demographic and CRM success factors. It was found that highest number of customers i.e. 35% of female customers are in the age group of 18-30 years and spent around Rs.1000- 5000 in shopping apparels during festival occasion